The rural-urban divide: Economic disparities and interactions in China - Knight, J; Song, L (Oxford University Press, 1999)
Describes the income and economic-welfare disparity between rural and urban China and investigates the economic policies and sectoral interactions that bring about the urban advantage. Provides a macroeconomic perspective on the income gap and its movement over time and considers the extent to which the gap is the result of urban bias in government policies. Analyzes the rural-urban income divide and its sources from a microeconomic perspective, and investigates inequality within both urban and rural China, using data from a national household survey conducted in 1988. Provides rural-urban comparisons of welfare, focusing on education, health, and housing. Examines the transfer of capital between urban and rural areas. Analyzes the rural-urban migration of labor from a macroeconomic perspective. Provides a microeconomic analysis of the causes, processes, and consequences of rural-urban migration based on a survey undertaken in Handan municipality in Hebei province. Presents implications for policy, compares the Chinese case with that of other countries, and assesses the relevance of various theoretical models in explaining Chinese urban-rural relationships. Knight is Professor of Economics and Director, and Song is Research Officer, at the Institute of Economics and Statistics, University of Oxford. Name, subject, and province indexes.